E-learning interactions, information technology self efficacy and student achievement at the University of Sharjah, UAE - Abulibdeh, Enas Said; Syed Hassan, Sharifah Sariah (Australian Society for Educational Technology, 2011)

(untitled)
The purpose for this study is to validate a model of student interactions (student-content, student-instructor and student-student interactions and vicarious interaction), information technology self efficacy and student achievement. Investigation of the relationships was undertaken with structural equation modeling analyses, in a study with 250 undergraduate students providing 231 responses for the final analyses. Adopting a framework from Moore (1989) and Devries (1996) on e-learning interactions and Bandura (1997) on self efficacy, this study has found that student interactions can be predictors of student achievement. However, self-efficacy can only promote student achievement via student interactions in an e-learning environment. Although the hypothesised model showed an overall fit, it was further re-specified due to non significant relationships between IT self efficacy and student achievement. (Contains 1 figure and 6 tables.)